2017
DOI: 10.1016/j.jmb.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Sequence Necessary and Sufficient to Package Non-viral RNAs into HIV-1 Particles

Abstract: Genome packaging is an essential step to generate infectious HIV-1 virions and is mediated by interactions between the viral protein Gag and cis-acting elements in the full-length RNA. The sequence necessary and sufficient to allow RNA genome packaging into an HIV-1 particle has not been defined. Here, we used two distinct reporter systems to determine the HIV-1 sequence required for heterologous, non-viral RNAs to be packaged into viral particles. Although the 5' untranslated region (UTR) of the HIV-1 RNA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 77 publications
(75 reference statements)
3
36
0
Order By: Relevance
“…Additionally, this study does not investigate how Gag assembly is mediated by cellular RNAs, which can also bind to Gag to form VLPs, particularly in the absence of vRNA ( 9 11 ). Nonetheless, our results should still be relevant to understanding the HIV-1 assembly process, as vRNA is the dominant RNA species that drives Gag assembly ( 5 , 6 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, this study does not investigate how Gag assembly is mediated by cellular RNAs, which can also bind to Gag to form VLPs, particularly in the absence of vRNA ( 9 11 ). Nonetheless, our results should still be relevant to understanding the HIV-1 assembly process, as vRNA is the dominant RNA species that drives Gag assembly ( 5 , 6 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 92%
“…Together, these findings suggest that upon binding of monomeric Gag to the viral genome through Ψ, multimerization-dependent changes in the RNA binding specificity of Gag may drive the selective packaging of the A-rich viral genome. In line with this model, a recent study has shown that longer segments of the Gag ORF, but not Ψ alone, can gradually increase the packaging of heterologous RNAs into virions [ 80 ]. Thus as part of the selective RNA packaging process, the role of Gag-Ψ interaction may be to nucleate further assembly of Gag oligomers on the viral genome [ 81 ].…”
Section: Application Of Clip Techniques In Retrovirologymentioning
confidence: 90%
“…Deletion of nt 22 to 378 in gag does not substantially decrease infectious-virus production (15,47), indicating that there are no essential cis-acting elements in the region. However, altering the RNA sequence could modulate the local RNA structure in ways that a large deletion did not, and the 5= region of gag has been shown to indirectly regulate gRNA packaging by regulating the structure of the 5= UTR (48,49).…”
Section: Ficarelli Et Almentioning
confidence: 99%